Task-switching abilities in pre-manifest Huntington's disease subjects - Migliore, Simone; D'Aurizio, Giulia; Curcio, Giuseppe; Squitieri, Ferdinando (Parkinsonism & related disorders, 2019)
Huntington's Disease (HD) cognitive dysfunction occurs before unequivocal motor signs become apparent. The predominant early cognitive abnormal domains may include deficits in psychomotor speed, negative emotion recognition and executive functioning. Our study is aimed to investigate the executive control of cognition in pre-manifest (pre) HD subjects, by means of a task-switching protocol. We recruited 30 pre-HD subjects and 18 age-, sex- and education-matched Healthy Controls (HC). Subjects were assigned to two experimental groups: 15 pre-HD1 with a Total Motor Score (TMS) ≤4 (far from onset) and 15 pre-HD2 with a 5 ≤ TMS≤9 (near to onset and Diagnostic Confidence Level (DCL) still<4). Two different tasks were performed in rapid and random succession, so that the task was either changed from one trial to the next one (switch trials) or repeated (repetition trials). Switch trials are usually slower than repetitions, causing a so-called Switch Cost (SC). Pre-HD subjects had worse performance than HC in the switch and repetition trials, as indicated by increased SC and reaction times. In particular, pre-HD2 showed impaired switching abilities with reaction times slower than pre-HD1 and HC. Our study highlighted a task-switching impairment since HD was still at a pre-manifest stage. Such abnormalities worsen when pre-HD subjects start to show subtle motor manifestations, still nonspecific and insufficient to define the clinical diagnosis of HD (DCL<4). Considering that such abilities have obvious implications for activities of daily living, early cognitive rehabilitation programs addressing such deficits might be useful in the premanifest stage of the disease. •Early impaired task-switching in premanifest stage of HD.•Increased reaction times both in switch and repetition trials.•Closer to fully manifest HD, more impaired is the task-switching performance.•Future cognitive rehabilitation might focus on such abilities.